User Training and Education, Personal Technical Ability, Top Management Support and AIS Performance at LPD in South Kuta District (E-Jurnal Akuntansi, 2026)
This study aims to test and analyze the training and education program for users, personal technical skills, and top management support towards the performance of SIA employees at LPD Kuta Selatan District. The sample size in this study was 40 employees. The sampling technique used in this research was purposive sampling, which is a technique for determining samples based on specific considerations. Data analysis in this study was conducted using SPSS 25 software. The data analysis method used was multiple linear regression to test and prove the research hypotheses. The results of the study indicate that the ability of the training and education program for users and personal technical skills does not have a significant effect on SIA performance, while top management support has a significant effect on SIA performance. This can be observed from the probability values > and < 0.05.
Keywords: The Ability of Users; Training and Education of Users; Top Management Support; The Performance of Accounting Information System